Membangun Budaya Literasi Baca di UPT SD Inpres Bert Kaluku Bodoa - Syamsul Alam; Nurhadifah Amaliyah; Mutmainna Mutmainna; Fitriani Fitriani; Sri Wulandari (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
schools in carrying out reading literacy at the Inpres Bert Kaluku Bodoa Elementary School. Reading is an important thing in the teaching and learning process. Reading is the process of absorbing knowledge through reading or writing. Each student has abilities that vary from fast, medium and slow in terms of reading. This study aims to increase the need for habituation in students in increasing interest in reading. future at SD Inpres Bert Kaluku Bodoa. With some data and documenting the results of